'Masterstroke: a pilot group stroke prevention program for community dwelling stroke survivors'. (June 2013) - White, Jennifer H.; Bynon, Bridget L.; Marquez, Jodie; Sweetapple, Anne; Pollack, Michael
<x xml:space="preserve">Abstract</x> Objectives: To explore whether a pilot secondary stroke prevention group program for community-dwelling chronic stroke survivors assisted participants in modifying their lifestyle to reduce their risk of secondary stroke. Design: A mixed methods study (quantitative and qualitative). Setting: Community. Subjects: Twenty-two community dwelling, chronic stroke survivors. Intervention: The Masterstroke program incorporated a secondary prevention stroke group program over a 9-week period with two 2-h sessions weekly (1 hour for education and 1 hour for exercise). The exercise component incorporated fitness, strength, mobility and balance and education focused on secondary stroke prevention whilst also providing chronic condition self-management support. Main measures: Timed Up and Go (TUG), Six Minute Walk Test (6MWT), Fat and Fibre Barometer, The Stroke and Aphasia Quality of Life Scale (SaQoL-39), and questionnaires for salt intake and stroke knowledge. Qualitative outcomes were participants' perceptions. Data analysis involved an inductive thematic approach with constant comparison. Results: There were insufficient participants for results to reach statistical significance in all categories, however, statistically significant results where achieved with regards to knowledge, TUG, salt intake and quality of life (QoL) scores. Qualitative responses explored participants' experience of the Masterstroke program; results confirmed increases in knowledge about stroke and exercise tolerance, successfulness of a group program and lifestyle modification post stroke. Conclusions: Participation in the Masterstroke program for community dwelling stroke survivors resulted in significant improvements in knowledge, functional balance, dietary behaviours and quality of life. Qualitative interviews support the participants' implementation of lifestyle changes essential for reducing risks of secondary stroke. Results support the utilisation of this model and warrants rigorous investigation regarding long-term impacts of an education and exercise program on community dwelling stroke survivors.